200k views
2 votes
Evaluate: −4 + 12 ÷(−3)/10 + 3(−2)

User Plonetheus
by
5.3k points

2 Answers

3 votes

Answer:

Explanation:

First we calculate (-3)÷10 = -0.3

Then 12÷(-0.3) = -40

After that -4 + (-40) = -44

3(-2) = -6

Finally -44 + (-6) = -50

User NTDLS
by
5.8k points
1 vote

For this case we have that the order of algebraic operations is determined by PEMDAS:

P: Perform any calculation inside the parentheses, making the most internal ones first.

E: Simplify any exponential expressions.

MD: Do all the multiplications and divisions, from left to right, as they appear.

AS: Do all the addition and subtraction, from left to right, as they appear.

Then, we have the following expression:

-4 + 12 ÷ (-3) ÷ 10 + 3 (-2) =

-4-4 ÷ 10 + 3 (-2) =

-4-0.4 + 3 (-2) =

-4-0.4-6 =

-4.4-6 =

-10.4

Answer:

-10.4

User Chuacw
by
5.1k points